Autophagy Is Differentially Regulated in Leukocyte and Nonleukocyte Foam Cells During Atherosclerosis. Issue 6 (18th March 2022) - Robichaud, Sabrina; Rasheed, Adil; Pietrangelo, Antonietta; Doyoung Kim, Anne; Boucher, Dominique M.; Emerton, Christina; Vijithakumar, Viyashini; Gharibeh, Lara; Fairman, Garrett; Mak, Esther; Nguyen, My-Anh; Geoffrion, Michele; et al.
Abstract : Rationale: Atherosclerosis is characterized by an accumulation of foam cells within the arterial wall, resulting from excess cholesterol uptake and buildup of cytosolic lipid droplets (LDs). Autophagy promotes LD clearance by freeing stored cholesterol for efflux, a process that has been shown to be atheroprotective. While the role of autophagy in LD catabolism has been studied in macrophage-derived foam cells, this has remained unexplored in vascular smooth muscle cell (VSMC)-derived foam cells that constitute a large fraction of foam cells within atherosclerotic lesions. Objective: We performed a comparative analysis of autophagy flux in lipid-rich aortic intimal populations to determine whether VSMC-derived foam cells metabolize LDs similarly to their macrophage counterparts. Methods and Results: Atherosclerosis was induced in GFP-LC3 (microtubule-associated proteins 1A/1B light chain 3) transgenic mice by PCSK9 (proprotein convertase subtilisin/kexin type 9)-adeno-associated viral injection and Western diet feeding. Using flow cytometry of aortic digests, we observed a significant increase in dysfunctional autophagy of VSMC-derived foam cells during atherogenesis relative to macrophage-derived foam cells. Using cell culture models of lipid-loaded VSMCs and macrophages, we show that autophagy-mediated cholesterol efflux from VSMC foam cells was poor relative to macrophage foam cells, and largely occurs when HDL (high-density lipoprotein) was used as a cholesterol acceptor, as opposed to apoA-1 (apolipoproteinA-1). This was associated with the predominant expression of ABCG1 in VSMC foam cells. Using metformin, an autophagy activator, cholesterol efflux to HDL was significantly increased in VSMC, but not in macrophage, foam cells. Conclusions: These data demonstrate that VSMC and macrophage foam cells perform cholesterol efflux by distinct mechanisms, and that autophagy flux is highly impaired in VSMC foam cells, but can be induced by pharmacological means. Further investigation is warranted into targeting autophagy specifically in VSMC foam cells, the predominant foam cell subtype of advanced atherosclerotic plaques, to promote reverse cholesterol transport and resolution of the atherosclerotic plaque. Abstract : Supplemental Digital Content is available in the text.